URGENSI PENDIDIKAN DALAM MENGEMBANGKAN POTENSI DIRI ANAK - Harbeng Masni (Jurnal Ilmiah Dikdaya, 2018)
Potential is a basic capability that has not been revealed. Every human being has the potential to develop himself differently. For the disclosure it required a condition outside of himself. Educational institution is a formal institution that has the main task to reveal and develop the potential of each learners, therefore in coaching and evaluation of learners should use an individual approach, not general. Developments experienced and experienced by individual students. While education is an interaction. In the interaction activities, educators or teachers act to educate the students or students. The act of educating is focused on the development of students become independent through the learning process. In general, developmental theories revolve around issues related to innate and environmental influences for individual development. Active in the sense of learners must be conditioned actively by nature, active because of the impulse from within himself naturally, for that required conditions that are individual. Coaching and evaluation are applied individually. The academic potential, talents and interests of learners are really taken into account, therefore rewards in various forms, such as awarding certificates, stickers symbolizing appreciation of achievement for various subject areas, even if necessary, rewarding, facilitating as much as possible all academic achievements, talents and interests rather than learners. The teacher looks at the potential / academic achievements, talents and interests that run naturally, to further develop. The learners are not forced to master a particular field that has been applied by the institution or government (general), the ability is the ability of himself naturally, not because of the pressures that burden the learner and also that will cause the parents worries. All conditioned naturally, naturally, the recognition of the ability of self-implanted early so that no need to push yourself beyond ability. Each individual has their respective advantages, the problem is how to utilize that ability, whatever the form.